2008
DOI: 10.1007/s00467-008-0907-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal scar in children with urinary infection and vesicoureteral reflux

Abstract: We evaluated the predictors of renal scar in children with urinary tract infections (UTIs) having primary vesicoureteral reflux (VUR). Data of patients who were examined by dimercaptosuccinic acid (DMSA) scintigraphy between 1995 and 2005 were evaluated retrospectively. Gender, age, reflux grade, presence/development of scarring, breakthrough UTIs, and resolution of reflux, were recorded. The relation of gender, age and VUR grade to preformed scarring and the relation of gender, age, VUR grade, presence of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 26 publications
2
22
1
6
Order By: Relevance
“…2 Similar result was found by Zaki et al 31 In our study, the incidence and severity of grades of VUR in children is higher than the studies done by Chand et al and Zaki et al 2,31 The lack of antenatal sonologic evaluation and late referral of the patients are the two important risk factors that differs the present study with others. 32,33 In our study grade III-V reflux was present in 31 renal units which comprises 88.56% of the refluxing units .This figure is much higher than the study by Orellana P et al where moderate to severe grades were present in43.16% kidneys. 32 The higher incidence of reflux with advanced grades in our study again reflects parental ignorance and late referral of the patients who ultimately reach at our center with advanced stage of the disease.…”
Section: Discussioncontrasting
confidence: 46%
“…2 Similar result was found by Zaki et al 31 In our study, the incidence and severity of grades of VUR in children is higher than the studies done by Chand et al and Zaki et al 2,31 The lack of antenatal sonologic evaluation and late referral of the patients are the two important risk factors that differs the present study with others. 32,33 In our study grade III-V reflux was present in 31 renal units which comprises 88.56% of the refluxing units .This figure is much higher than the study by Orellana P et al where moderate to severe grades were present in43.16% kidneys. 32 The higher incidence of reflux with advanced grades in our study again reflects parental ignorance and late referral of the patients who ultimately reach at our center with advanced stage of the disease.…”
Section: Discussioncontrasting
confidence: 46%
“…Biggi et al [18], Fernández-Menéndez et al [5] and Soylu et al [20] found an association between high grade VUR and an abnormal DMSA renal scan. Although VUR is a famous predisposing factor for the development of APN, some recent studies have questioned such predisposition.…”
Section: Discussionmentioning
confidence: 97%
“…Risk factors for renal scarring are VUR, UTI, and previous scar/dysplasia. 5,6 Although antenatal US can help identify up to 30% of newborns with VUR, exposing detectable renal damage prior to UTI, US imaging can miss detection of approximately half of the scars. In accordance with this data, US was normal in 44% of our patients with abnormal DMSA.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with our previous data that the most important predictor of new/progressive scarring is the presence of renal scar. 6 Reflux nephropathy has been associated with longterm renal dysfunction like proteinuria and/or renal insufficiency. 7,9,10,14 Neither medical nor surgical treatment of VUR prevented renal function deterioration.…”
Section: Discussionmentioning
confidence: 99%